2000
DOI: 10.1002/(sici)1099-0682(200005)2000:5<801::aid-ejic801>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Titanosilicates and other Novel Mixed Octahedral-Tetrahedral Framework Oxides

Abstract: Stable microporous materials, such as zeolites, are extremely important for applications in catalysis, adsorption, ion‐exchange, and separation. In this review we describe a new class of stable microporous materials that involves novel mixed octhaedral‐tetrahedral framework oxides. The archetypal material is based on titanosilicates, although there is tremendous scope for introducing many other transition metals. These materials not only have potential novel applications in the fields normally associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
160
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(164 citation statements)
references
References 86 publications
1
160
0
3
Order By: Relevance
“…As-synthesized ETS-4 has been reported to collapse near 200 8C to an amorphous material owing to the loss of structural water chains present along the channel system 15 . We found that carefully controlled heating leads to a monotonic decrease of the lattice dimensions in all three crystallographic directions, along with the gradual loss of crystallinity.…”
mentioning
confidence: 99%
“…As-synthesized ETS-4 has been reported to collapse near 200 8C to an amorphous material owing to the loss of structural water chains present along the channel system 15 . We found that carefully controlled heating leads to a monotonic decrease of the lattice dimensions in all three crystallographic directions, along with the gradual loss of crystallinity.…”
mentioning
confidence: 99%
“…Its structure contains titanosilicate layers built of small cage-type units, each one containing eight tetrahedral SiO 4 units and one square-pyramidal TiO 5 polyhedron. 6 This makes JDF-L1 a promising material for oxidation catalysis. 5 The JDF-L1 layered structure allows pillaring as demonstrated by the successful intercalation of nonylamine.…”
mentioning
confidence: 99%
“…This is the field of zeolites [31,123] and zeotypes [124,125] that are nanoporous crystalline systems constituted by corner-sharing [TO 4 ] tetrahedra (T ¼ Si, Al or P mainly) exhibiting pores of molecular dimension (0.5e1.5 nm range). This is the field of zeolites [31,123] and zeotypes [124,125] that are nanoporous crystalline systems constituted by corner-sharing [TO 4 ] tetrahedra (T ¼ Si, Al or P mainly) exhibiting pores of molecular dimension (0.5e1.5 nm range).…”
Section: Heterostructures and Nanostructures: Definition And Applicatmentioning
confidence: 99%